Streptococcus sinensis Causing Tricuspid Endocarditis in a Child: An Unusual Pathogen at an Unusual Site: A Case Report with Review of Literature - Navya Sree Manugu; Manisha Varma Gadhiraju; Stephen Chityala; Kodandapani Yerroju; Sadanand Reddy Tummala (Wolters Kluwer Medknow Publications, 2024)
Background: Infective endocarditis (IE) involving tricuspid valve is rarely reported in children. Common etiological organisms of IE include Staphylococci, viridans group Streptococci, and Enterococci. Other less frequent organisms include Haemophilus, Actinobacillus, Cardiobacterium, Eikenella, and Kingella (HACEK) group, and Candida, accounting for 1% of cases. We describe the rare case scenario of tricuspid valve endocarditis caused by an unusual pathogen. Clinical Description: An 8-year-old girl presented with complaints of cough, shortness of breath, and intermittent fever for the past 2 months. Since 10 days before presentation, the fever had become high grade, continuous, and associated with chills and rigors. As per parents, the child had incidentally been detected with some congenital heart disease (CHD) at 3 months of age, documents being unavailable, child remaining asymptomatic till this presentation, without any medications. On examination, the child was malnourished with pallor, Grade 3 clubbing, tachypnea, and tachycardia. Auscultation revealed bilateral basal crepitations and a pansystolic murmur of Grade 4 in tricuspid area. Management and Outcome: Along with routine investigations, a two-dimensional echocardiography was done which revealed perimembranous ventricular septal defect with left-to-right shunt, tricuspid valve vegetations with anterior tricuspid leaflet prolapse with ruptured chordea, severe tricuspid regurgitation, and thickened aortic valve with good biventricular function. Blood culture showed growth of Streptococcus sinensis. The child was treated with oxygen, diuretics, and intravenous ciprofloxacin and gentamicin according to antibiotic sensitivity pattern. The child became hemodynamically stable and symptomatically improved after 3 weeks of treatment. Conclusion: This case creates awareness regarding an usual pathogen - S. sinensis as an etiological agent of IE, involving an unusual site - the tricuspid valve, in a child with CHD.